A regulatory subunit of the cAMP-dependent protein kinase down-regulated in aplysia sensory neurons during long-term sensitization. - Bergold, P; Beushausen, SA; Sacktor, T; Cheley, S; Bayley, H; Schwartz, J (1992)
Binding of cAMP by the five neuronal isoforms (N1-5) of the regulatory (R) subunit of the Aplysia cAMP-dependent protein kinase is diminished in sensory neurons stimulated to produce long-term presynaptic facilitation. To determine how the cAMP-binding activity of the R subunits is lost, we isolated cDNAs encoding N4, which is a homolog of mammalian RI. Immunoblots with antisera raised against the R protein overexpressed in E. coli show that the diminished binding activity, which occurs in long-term facilitation, results from coordinate loss of R protein isoforms. No change was detected in the amount of transcripts for R subunits, suggesting that the down-regulation results from enhanced proteolytic turnover.